The Effect of Consumer Innovativeness, Perceived Benefits, Perceived Risk, and Brand Image in the Decision to Buy Online (Recoletos Multidisciplinary Research Journal, 2018)
With the advancing technology, online shopping is pacing fast. This calls for looking into factors that influence a consumer?s decision to buy online. With this, the present study investigated four variables namely consumer innovativeness, perceived benefit, perceived risk, and brand image and its impact toward consumer?s decision to buy online. To address this aim, four hundred eighty (480) participants were recruited online and randomly assigned into one of the sixteen treatment conditions with the presence and/or absence of the four variables being investigated. Results of two-way analysis of variance showed that, in an online selling platform, the presence of consumer innovativeness and perceived benefit, the presence of perceived benefit and perceived risk, and brand image had significant influence in one?s decision to buy online. Findings provide implications towards improving an online website?s shopping platform which may motivate the consumer to buy.
Keywords: online shopping; consumer innovativeness; perceived benefit; perceived risk; brand image